Private Sector Actions to Valorise Public Benefits from Agriculture and Forestry. (5th June 2018) - Brouwer, Floor; Mantino, Francesco; Polman, Nico; Short, Chris; Sterly, Simone; Rac, Ilona
Summary: There is wide consensus that the agricultural and forestry sectors play an important role in the provision of public benefits. Major changes are envisaged by some in the future developments of the Common Agricultural Policy (CAP) regarding the provision of these benefits. However, while policy can be a powerful driver for change, it is often not sufficient to trigger action by itself; new approaches are required to increase the engagement and commitment of actors in this field. The PEGASUS project aimed to understand new ways of thinking about the way farmland and forests are managed to stimulate long‐lasting improvement in the provision of public benefits in the EU. Since the private sector is already actively involved in securing the provision of public benefits e.g. through premium price mechanisms, this article seeks to outline private sector actions for the more effective provision of public benefits arising from EU farmland and forests. The article suggests a number of approaches to be considered when developing policy that seeks to encourage the involvement of the private sector. Abstract : There is wide consensus that the agricultural and forestry sectors play an important role in the provision of public benefits. Major changes are envisaged by some in the future developments of the Common Agricultural Policy (CAP) regarding the provision of these benefits. However, while policy can be a powerful driver for change, it is often not sufficient to trigger action by itself; new approaches are required to increase the engagement and commitment of actors in this field. The PEGASUS project aimed to understand new ways of thinking about the way farmland and forests are managed to stimulate long‐lasting improvement in the provision of public benefits in the EU.